Development of Predict-Observe-Explain (POE) Strategy Assisted by Rebuttal Texts on Newton's Law Material with Rasch Analysis - Samsudin, Achmad; Rusdiana, Dadi; Efendi, Ridwan; Fratiwi, Nuzulira Janeusse; Aminudin, Adam Hadiana; Adimayuda, Rizal (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aimed to develop Predict-Observe-Explain (POE) strategy with refutation text based on Newton's Law. The research design used was 4D (Define, Design, Develop, and Disseminate). The participants consisted of 31 students (15 male students and 16 female students) with an age range of 15-16 years selected from the tenth grade of a public high school in Sukabumi, Indonesia. The instruments used were lesson plan validation sheets and a questionnaire containing 20 statements (11 positive and nine negative statements) with a Likert scale. The scores for positive statements move sequentially from four to one, while the scores for negative statements move sequentially from one to four. The analysis used in this study was the Rasch analysis. As a result, the lesson plan's codes for indicators have an unrevised assessment, while the Language, Concept, Strategy, Objective, and Time codes must be revised. The student responses indicated that all students did not agree with all negative statements, except for S26, S07, S28, and S01. Meanwhile, all students agreed to all positive statements given. Thus, it can be concluded that the POE strategy assisted by rebuttal text can better help students to understand Newton's Law material.